ANTIMALARIAL AND ANTIOXIDANT EFFECTS OF Persea Americana (avocado) LEAF EXTRACT IN Plasmodium berghei-INFECTED MICE (FUDMA JOURNAL OF SCIENCES, 2025)
The emergence of drug-resistant Plasmodium strains necessitates the search for alternative treatment strategies, including plant-derived bioactive compounds with antimalarial and antioxidant properties. Persea americana (avocado) leaves have been reported to possess medicinal benefits, but their antimalarial potential remains underexplored. This study evaluates the antimalarial and antioxidant effects of P. americana leaf extract in Plasmodium berghei-infected mice. Mice infected with P. berghei were treated with varying doses of the extract, and body weight, rectal temperature, packed cell volume (PCV), parasitemia levels, and oxidative stress markers were assessed. Results demonstrated a significant improvement in body weight and PCV, as well as reductions in rectal temperature, parasitemia, improved parasite clearance, and enhanced antioxidant enzyme activity in treated groups compared to the untreated control. These findings suggest that P. americana leaf extract possesses potent antimalarial and antioxidant properties, supporting its potential as a complementary therapeutic agent. Further studies are needed to elucidate its mechanisms of action and optimize dosage for clinical applications. This study contributes to the ongoing search for plant-based alternatives in malaria treatment and oxidative stress management.
Keywords: Antimalaria; Antioxidant; Persea Americana; Oxidative stress